Arsenic trioxide-induced cardiotoxicity triggers ferroptosis in cardiomyoblast cells. (23rd February 2022) - Wang, Linya; Liu, Shuguang; Gao, Chao; Chen, Hui; Li, Jing; Lu, Jiran; Yuan, Yuan; Zheng, Xueling; He, Hongbo; Zhang, Xixi; Zhang, Ruidong; Zhang, Yuanyuan; et al.
Arsenic trioxide (ATO) has been found to be effective in acute promyelocytic leukemia. However, ATO-induced severe cardiotoxicity limits its clinical application. To date, the mechanisms of ATO-induced cardiotoxicity remain unclear. It is hypothesized that ferroptosis may trigger ATO-induced cardiotoxicity; however, this has not yet been investigated. To clarify this hypothesis, rat cardiomyocyte H9c2 cells were treated with ATO with or without ferrostain-1 (Fer-1). The results indicated that ATO exposure induced H9c2 cell death and apoptosis, and the ferroptosis inhibitor Fer-1, administered for 24 h before ATO exposure, suppressed ATO-induced cell death, and apoptosis, as determined by Annexin V-APC/7-AAD apoptosis assay. Furthermore, Fer-1 displayed a cardioprotective effect through inhibiting the ATO-induced production of intracellular reactive oxygen species, improving the ATO-induced loss of the mitochondrial membrane potential, alleviating hyperactive endoplasmic reticulum stress, and alleviating the ATO-induced impairment in autophagy in H9c2 cells. Overall, the cardioprotective effect of Fer-1 against ATO-induced cell injury implies that ATO may trigger ferroptosis to induce cardiotoxicity. These findings lay the foundation for exploring the potential value of ferroptosis inhibitors against ATO-induced cardiotoxicity in the future.